Industrial Training Report: Perpustakaan Sultanah Nur Zahirah Universiti Malaysia Terengganu / Wan Siti Nur Atieqah Wan Hanudin - Wan Hanudin, Wan Siti Nur Atieqah (Faculty of Information Management, 2016)
The industrial training subject IMC690 provides pre-professional work experience with specific assignment and responsibilities. The organization choose by the trainee is located at Perpustakaan Sultanah Nur Zahirah, Universiti Malaysia Terengganu. This report consists of five chapters. Chapter one is discussing on the background information of Universiti Malaysia Terengganu and Perpustakaan Sultanah Nur Zahirah. In this chapter also include the information about library's services, facilities and collection provided. Chapter two is focusing on the structure and function of each department in library. Then chapter 3 is about the training activities and project that have been done in this library. Chapter 4 is focusing on the description of project or task, skills, knowledge and experienced gained, personal thought and opinion, lesson learnt, and limitation and recommendation of practical training. The conclusion is the last chapter for this report which summarizes the whole report of practical training.